2017
DOI: 10.1161/circgenetics.116.001616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Selection Bias on Estimation of Subsequent Event Risk

Abstract: Background Studies of recurrent or subsequent disease events may be susceptible to bias due to selection of subjects who both experience and survive the primary indexing event. Currently, the magnitude of any selection bias, particularly for subsequent time-to-event analysis in genetic association studies, is unknown. Methods and Results We used empirically inspired simulation studies to explore the impact of selection bias on the marginal hazard ratio (HR) for risk of subsequent events among those with esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Selection into the study depends both on having an initial diagnosis and on surviving initial coronary events, so factors that influence survival may also confound analysis of prognosis. In a simulation study 15 , we showed that index event bias could be small in the GWAS context. Here we have confirmed this in the case of Crohn's disease, but have…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Selection into the study depends both on having an initial diagnosis and on surviving initial coronary events, so factors that influence survival may also confound analysis of prognosis. In a simulation study 15 , we showed that index event bias could be small in the GWAS context. Here we have confirmed this in the case of Crohn's disease, but have…”
Section: Discussionmentioning
confidence: 87%
“…Such approaches are difficult in genetic studies, because there may be a substantial polygenic confounder that cannot be modelled directly nor easily captured by a propensity score 11 . Recently, the implications of index event bias for genetic studies have been discussed in the contexts of association discovery 15 and Mendelian randomisation 2 . Although the magnitude of bias appears small in currently typical settings, it is unclear how GWAS will be affected as meta-analyses grow to greater orders of magnitude and polygenic analyses combine effects over thousands of variants.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins influencing the risk of a first event may also influence the risk of subsequent events, as observed in the case of the target of statin drugs that are effective in both primary and secondary prevention (1). For this and other reasons (34)(35)(36), examination of the effects of PCSK9 variants on the risk of subsequent CHD events in patients with established coronary atherosclerosis is the subject of a separate analysis led by the GENIUS-CHD consortium (36).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic randomization on genotype at conception means many years' worth of selective survival could occur before recruitment [4]. The possibility of bias in GWAS arising from survival on genotype, has been considered and is thought, from simulation, to have little effect on estimates of associations [5] before the age of 75 years [6].…”
Section: Introductionmentioning
confidence: 99%